2012
DOI: 10.1080/09585192.2011.561227
|View full text |Cite
|
Sign up to set email alerts
|

Does pay for performance diminish intrinsic interest?

Abstract: One concern with pay for individual performance (PFIP) is that it may undermine intrinsic interest, thus having little or no positive net influence on performance. A major basis for this concern is cognitive evaluation theory [CET; Deci and Ryan (1985), Intrinsic Motivation and Self-Determination in Human Behavior, New York: Plenum Press]. Most evidence on CET, however, comes from non-work settings and, even in that arena, there is debate regarding the undermining effect of PFIP. There is little workplacebased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 59 publications
10
86
1
6
Order By: Relevance
“…Fang and Gerhart (2012) recently obtained results that are different from ours. In a study of white collar workers from eight different Taiwanese companies, they found that variable PFP (as reported by HR managers)…”
Section: Discussioncontrasting
confidence: 46%
“…Fang and Gerhart (2012) recently obtained results that are different from ours. In a study of white collar workers from eight different Taiwanese companies, they found that variable PFP (as reported by HR managers)…”
Section: Discussioncontrasting
confidence: 46%
“…Although pay‐for‐performance rewards may come to mind as an example of controlling rewards (Ryan et al, ), such rewards may in actuality be ambiguous (Fang & Gerhart, ). The reason is that such rewards simultaneously convey competence‐affirmative information and demand that individuals perform up to a given standard.…”
Section: Motivation For Knowledge Sharing and The Impact Of Internal mentioning
confidence: 99%
“…In contrast, when the informational value of a reward outweighs the controlling effects, feelings of self-determination are not necessarily reduced but can also increase and lead to better creative performance (Eisenberger and Cameron, 1996;Eisenberger and Shanock, 2003). In economics, crowding-out effects have so far been studied mainly in the context of intrinsically motivated activities other than creative tasks (see Frey and Jegen, 2001, for an overview) and the existence of crowding-out effects is controversially debated (for instance, Fang and Gerhart, 2012;Fehr and Falk, 2002;Charness and Gneezy, 2009;Charness and Grieco, 2013). In order to check for potential crowding-out effects of the piece rate incentive, individual productivity is measured (1) without reward and (2) under a piece rate incentive.…”
Section: The Experimental Set-upmentioning
confidence: 99%